Yellowish oral mass occurring after nasolabial dermal filler - Lombardi Niccolò; Lodi Giovanni (EDP Sciences, 2024)
Intra-oral lesion of the lower lip occurred two months after nasolabial folds dermal filler. The lesion appeared as a yellowish submucosal painless mass of approximately 15mm on the intraoral side of the inferior lip. An incisional biopsy was performed and definitive diagnosis of foreign body reaction to calcium hydroxyapatite was made. The lesion underwent complete spontaneous regression within eight months.